Philip and Alexander : kings and conquerors - Goldsworthy, Adrian Keith (Basic Books, 2020)
"Alexander the Great's conquests staggered the world. He led his army across thousands of miles, from northern Greece to modern Pakistan, overthrowing the greatest empires of his time and building a new one in their place. He led from the front and was often wounded. He claimed to be the son of a god, but he was actually the son of Philip II. In Philip and Alexander: Kings and Conquerors, classical historian Adrian Goldsworthy argues that without the work and influence of his father, it is very doubtful that Alexander would have achieved so much. Philip II of Macedon is often remembered as an old man, one-eyed and lame from wounds. But he was young and inexperienced when he came to power. Philip inherited a minor kingdom that was on the verge of being dismembered. He succeeded in making Macedonia dominant throughout Greece and preparing Alexander to lead his army into war against Persia. Philip, Goldsworthy shows, created the armies that won Alexander's victories. A bold new interpretation, Philip and Alexander will be the definitive dual biography of two men who together reshaped the ancient world."--